1952
DOI: 10.6028/jres.048.056
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of D-mannitol-C-14 and its conversion to D-fructose-1-(and 6)-C-14 by acetobacter suboxydans

Abstract: Methods are described for t he produc tion of D-mannitol-l-C14 and D-fructose-l-(and 6)-C14. .These matermls ar e powerful new tools for research in biology and chemistry. D-Manmtol-l-C14 was prepared in SO-percent yield from D-mannono-'Y-lactone. D-Fructosel-(and 6)-C14 was produced in 54-percent yield by growth of Acetobacter suboxydans on a D-Mannitol-l-C '4 substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1956
1956
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In the periodate oxidation of the disaccharide methyl glycoside obtained by reduction of aldobiouronic acid II 2.9 moles of periodate was consumed and 1.16 moles of formic acid was produced. These data fitted the requirements for a glucose unit linked glycosidically to a xylopyranoside unit through C (2) or C»)• Similar oxidation of the disaccharide methyl glycoside from aldobiouronic acid (1) Presented in part before the Division of Cellulose Chemistry, 128th Meeting, American Chemical Society, Minneapolis, Minn., 1955.…”
Section: Introductionmentioning
confidence: 66%
“…In the periodate oxidation of the disaccharide methyl glycoside obtained by reduction of aldobiouronic acid II 2.9 moles of periodate was consumed and 1.16 moles of formic acid was produced. These data fitted the requirements for a glucose unit linked glycosidically to a xylopyranoside unit through C (2) or C»)• Similar oxidation of the disaccharide methyl glycoside from aldobiouronic acid (1) Presented in part before the Division of Cellulose Chemistry, 128th Meeting, American Chemical Society, Minneapolis, Minn., 1955.…”
Section: Introductionmentioning
confidence: 66%
“…Previously, d -mannitol- 1-C 14 had been oxidized by A. suboxydans to d -fructose- 1 , 6 - C 14 [ 3 ], and the isotopic distribution in the latter compound had been determined [ 4 ]. 5 In the present study, d -mannitols labeled either with carbon-14 at C1, C2, or C3, or with tritium attached to C1, C2, or C3, were prepared and were then oxidized by A. suboxydans.…”
Section: Introduction and Discussionmentioning
confidence: 99%
“… 11 In their preparation of d -fructose- 1,6-C 14 , Isbell and Karabinos [ 3 ] determined both the total reducing-substance and the d -fructose (the latter by polarization at two temperatures). They showed that the maxima for the two occur at approximately the same time.…”
mentioning
confidence: 99%
“…With a surface: volume ratio of 1:195, Fulmer et al (1939) found that mannitol concentrations up to and including 25 per cent weight per volume (w/v) were consistently converted to fructose to the extent of 90 per cent or better of theoretical in 7 days or less. The findings of Fulmer et al (1939) were confirmed by the work of Isbell and Karabinos (1952), but only with regard to low mannitol concentrations (less than 5 per cent). As far as is known, these surfaceculture laboratory-scale investigations are the only published reports available on the conversion of mannitol to fructose by A. suboxydans.…”
mentioning
confidence: 81%
“…The conversion of D-mannitol to D-fructose by the oxidative action of A. suboxydans, which was first reported by Bertrand (1904), has also been studied but to a considerably lesser extent. Laboratory-scale studies on this conversion under surfaceculture fermentation conditions were first reported by Fulmer et al (1939) and more recently by Isbell and Karabinos (1952). With a surface: volume ratio of 1:195, Fulmer et al (1939) found that mannitol concentrations up to and including 25 per cent weight per volume (w/v) were consistently converted to fructose to the extent of 90 per cent or better of theoretical in 7 days or less.…”
mentioning
confidence: 95%